Axial compressive behavior of lithium slag and rubber concrete-filled steel tube stub columns - Ying Yang; Jiongfeng Liang; Wanjie Zou; Caisen Wang; Jicheng Liu (PLoS ONE, 2025)
In order to solve the harm of industrial waste such as lithium slag and waste rubber to the environment, this paper put forward the structure of lithium slag and rubber concrete-filled steel tube (LSRuCFST) stub column, which was replaced cement and sand in concrete by lithium slag and waste rubber respectively. Through the axial compression test of 11 LSRuCFST specimens with various lithium slag replacement ratios (0, 10%, 20%, 30%) and rubber replacement ratios (0, 5%, 10%, 20%, 30%), the damage patterns and mechanical characteristics of LSRuCFST columns were studied. The experimental phenomena showed that the damage patterns of 11 specimens were similar to the ordinary concrete-filled steel tube (CFST) colunms. With 20% replacement ratio of lithium slag and 10% replacement ratio of rubber, the largest increase of bearing capacity was optimal. Then, the bearing capacities of LSRuCFST columns were investigated by domestic and international standards. Due to conservative predicted results, a modified computational formal for the LSRuCFST column bearing capacity was presented and verified by the test results of references.